Malunited supracondylar femur fracture in haemophilia A: a case report on evaluation and management - Sharma, Swati; Kumar, Amit; Sharma, Sanjay (International Journal of Research in Orthopaedics, 2023)
Haemophilia is a rare inherited X-linked bleeding disorder associated with various levels of coagulation factor VIII (type A) or IX (type B) deficit. Hemophilic patients can be affected by trauma and fractures just like the general population. But due to their bleeding disorder, such patients need specific multidisciplinary management, from the emergency room to the operating theatre, in order to limit severe complications. The goal of modern fracture treatment is to obtain an optimal outcome, with the patient’s return to full activity as soon as possible. If a fracture is correctly treated in a haemophilic patient, it will progress to consolidation in a similar time-frame to fractures occurring in the general population. Worldwide, there are only a few specialized orthopaedic centres dedicated to the management of hemophilia. Management of supracondylar femur fracture in patients with haemophilia is no different from general population if an adequate haemostasis is achieved. The purpose of this paper is to report our experience on the supracondylar fracture of the femur in hemophilia by a multidisciplinary team at a single institution.